Enraizamento de Eucalyptus grandis x Eucalyptus urophylla pela ação de peróxido de hidrogênio, quercetina e ácido indolbutírico - Prado, Débora Zanoni do [UNESP] (2014)
Vegetative propagation is the main form to produce cuttings of Eucalyptus, but some clones still have difficulties in propagation, including on rooting process. Indirectly, flavonoids and hydrogen peroxide can enhance this process, as well as modify the levels of antioxidants such as phenolic compounds and enzymes. This work was aimed to evaluate flavonoid quercetin, hydrogen peroxide and indolbutyric acid (IBA) action on rooting of cuttings of Eucalyptus grandis x urophylla, as well as in mechanisms of antioxidants production and cells protection against oxidative damage. The study was divided into two phases. Initially, clones were subjected to treatments with combination of hydrogen peroxide (0, 1.75, 3.5 and 7.0%) and IBA (0, 1.000 mg kg-1) and combination of quercetin (0, 250, 500, 1.000 mg kg-1) and IBA (0, 1.000 mg kg-1). Treatments were applied to cuttings and evaluated in thirty, sixty and ninety days after planting in relation to height, diameter and survival percentage. Ninety days after planting, a destructive evaluation was performed and percentage of rooting, average size of the largest root and the amount of roots were determined. After this evaluation, hydrogen peroxide (0, 3.5%), IBA (0, 1000 mg kg-1) and quercetin (0,500 mg kg-1) were combined in order to verify the interaction of hydrogen peroxide, quercetin and IBA on some molecules with antioxidant capacity. Ninety days after planting, these compounds effects on the activity of IAA oxidase, peroxidase, polyphenol oxidase, phenylalanine ammonia lyase and polyamine oxidase and the levels of phenolics, flavonoids, anthocyanins and polyamines were evaluated by spectrophotometric methods and levels of quercetin and indole acetic acid were evaluated via LC/MS in leaves and roots. Data were subjected to analysis of variance (ANOVA) and Tukey test at 5 % probability. No significant differences were found in relation to height, diameter, survival ...